A socio-economic study of Parkwood Estate, Cape Flats - Rabkin, Phyllys (Department of Social Development, 2016)
Parkwood Estate in the municipality of Cape Town is part of the Wynberg Ward. It is bounded on the west by the Prince George Drive, an arterial road to the False Bay Suburbs, on the north by the Golf Links Estate and on the other side by farmlands not as yet sub-divided into plots. Parkwood Estate, in spite of its prepossessing name, is a typical "pondokkie settlement" on the Cape Flats, housing some 1,100 people, mainly Coloured. The Estate is forty-three acres in extent and has about 185 houses, making it one of the more densely populated areas in the vicinity. The dwellings are of very poor construction, consisting almost entirely of roughly built wood and iron structures. The area is singularly deficient in municipal services, there being no system of sewerage and no provision for stormwater drainage. This latter municipal deficiency has meant that annual flooding is inevitable for the people of Parkwood but the seriousness of the consequences was only brought to the notice of the public in the winter of 1941 when the rains were particularly severe. The water level was so high that houses were rendered totally uninhabitable and two children in the district met their death through drowning. The conditions of life are backward, the roads are only tracks in the prevailing sandy littoral drift characteristic of the Cape Flats, the water supply is drawn from wells open to contamination, and the homes are illuminated at night by candlelight.